Water Symbolism in Yorùbá Folklore and Culture1 - George Olusola Ajibade (Yoruba Studies Review)
Water is not only a physical substance; it is also an intrinsic part of peoples’ identity, cultural perception, religious beliefs and worldviews. Water is a relevant and a significant variable that is also germane to the understanding of Yorùbá peoples’ identity, culture and religion. Hence, this ethnographical and literary study examines the image of water in Yorùbá cosmology using folklore (oral texts) of the people as paradigms. It uses a field investigative method of research to elicit primary data from the people on the uses of water in diverse spheres of life. It supplements oral data with secondary data in the form of books, journal articles and archival materials. The data collected was analysed from the lenses of a hermeneutical-anthropological approach. The study found that water constitutes and creates cultural, social and religious identities among the Yorùbá people of southwestern Nigeria. In addition, it concludes that water represents one of the several ways through which the Yorùbá society can be best understood.